THE IMPACT OF THE ONGOING RUSSIA–UKRAINE WAR ON THE EMOTIONAL STATE OF UKRAINIAN UNIVERSITY STUDENTS - Baran, I.V. (Sworld-Us Conference proceedings, 2025)
The article examines the impact of the Russian-Ukrainian war on the emotional state of student youth.